2014
DOI: 10.11130/jei.2014.29.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Air Cargo beyond Trade Barriers in Africa

Abstract: We develop a methodology based on two important criteria -sensitivity in delivery time and value-to-weight ratio -to classify air cargo products. The classification is applied to evaluate the trade integration in Southern Africa since air cargo is a valuable option to overcome trade barriers associated with poor land transport infrastructure and corruption. We find that South Africa's exports to industrialized countries consist of precious products such as diamonds and gold. These products tend to be transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…South Africa's excellent flight connections also matter for moving goods; albeit less bulky ones than those usually transported by rail and road -gold, platinum or even vegetables as opposed to coal. Dettmer, Freytag and Draper (2014) show that South Africa exports a much larger share of products with high air cargo relevance to Mozambique, Zambia and Zimbabwe than to industrialised countries. Hence, air cargo transport appears to be a valuable option to overcome trade barriers associated with land transport, including corruption at border stations (more on this in section 3.5).…”
Section: Box 3: or Tambo As A Central Air Hubmentioning
confidence: 97%
“…South Africa's excellent flight connections also matter for moving goods; albeit less bulky ones than those usually transported by rail and road -gold, platinum or even vegetables as opposed to coal. Dettmer, Freytag and Draper (2014) show that South Africa exports a much larger share of products with high air cargo relevance to Mozambique, Zambia and Zimbabwe than to industrialised countries. Hence, air cargo transport appears to be a valuable option to overcome trade barriers associated with land transport, including corruption at border stations (more on this in section 3.5).…”
Section: Box 3: or Tambo As A Central Air Hubmentioning
confidence: 97%
“…In their study on air cargo in South Africa, Dettmer et al (2014) concluded that a more liberal market for air cargo services could reduce transportation costs and encourage further integration. Despite the fact that ports have the greatest impact on trade (Nordas and Piermartini, 2004), port productivity may have a substantial impact on transportation costs.…”
Section: Definitionmentioning
confidence: 99%